PENGGUNAAN BEBERAPA TEORI MATRIKS DALAM TEORI GRAF - Amir, Amir Kamal (MATEMATIKA, 2010)
In a simple graf G, two veritces u and v are called adjacent in G if {u,v} ia an edge of G. The adjacency matrix A of G is the n x n zero-one matrix with 1 as its (i,j)th entry when vi and vj are adjacent, and 0 as its (i,j)th entry when they are notÂ  adjacent. In this paper will be described the characteristic of characteristic polynomial of a graph. Moreover, the relationship between the characteristic polynomial of a graph with characteristic polynomial of its subgraph will also be outlined. In addition, will also be described the shape of eigenvalues and eigenvectors of certain graph.